Suitability of Gareth Kershaw System Pantaloon Pattern on Tall-Fat Indonesian Adult Men - Kholizah, Kholizah; Nelmira, Weni (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
The Gareth Kershaw pantaloon pattern is not yet known whether it is suitable for tall, fat Indonesian adult men. The purpose of this study was to describe the weaknesses, how to improve, and adjust the Gareth Kershaw pantaloon pattern for tall, fat Indonesian men. The type of research used is applied research. The object of the study is the Gareth Kershaw pantaloon pattern, which was tested on tall, fat Indonesian adult men with a height of 178 cm and a weight of 73 kg. The research instrument used was a questionnaire using a Likert scale. The assessment was carried out by 3 panelists, namely those who were skilled and experts in men’s clothing. The data analysis technique used was descriptive statistics in the form of percentage formula calculations using Microsoft Excel. The results of the study showed that the Gareth Kershaw pantaloon pattern had weaknesses in the following sections: 1) hip circumference, 2) thigh circumference, 3) trouser length. The weaknesses were corrected in the pattern and trousers to produce a Gareth Kershaw pantaloon pattern that was suitable for tall, fat Indonesian adult men.